2021
DOI: 10.1126/science.abg6155
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian retrovirus-like protein PEG10 packages its own mRNA and can be pseudotyped for mRNA delivery

Abstract: Hitching a ride with a retroelement Retroviruses and retroelements have inserted their genetic code into mammalian genomes throughout evolution. Although many of these integrated virus-like sequences pose a threat to genomic integrity, some have been retooled by mammalian cells to perform essential roles in development. Segel et al . found that one of these retroviral-like proteins, PEG10, directly binds to and secretes its own mRNA in extracellular virus–like cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
271
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(276 citation statements)
references
References 59 publications
2
271
0
3
Order By: Relevance
“…A recently developed novel system for viral protein-mediated delivery and fusion with target cells is represented by the paternally expressed gene 10 (PEG10) [132] This gene product of retroelements as one of the mammalian gag homologs contributes to virus-like capsid formation that may also interact with cellular plasma membranes. Thereby, PEG10 can enable the transport of RNAs such as mRNAs and miRs among others into target cells [132,133]. Accordingly, the PEG10 system can deliver cargo to cells alternative to physiological vehicles like microvesicles or exosomes [134,135].…”
Section: Viral Fusogensmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently developed novel system for viral protein-mediated delivery and fusion with target cells is represented by the paternally expressed gene 10 (PEG10) [132] This gene product of retroelements as one of the mammalian gag homologs contributes to virus-like capsid formation that may also interact with cellular plasma membranes. Thereby, PEG10 can enable the transport of RNAs such as mRNAs and miRs among others into target cells [132,133]. Accordingly, the PEG10 system can deliver cargo to cells alternative to physiological vehicles like microvesicles or exosomes [134,135].…”
Section: Viral Fusogensmentioning
confidence: 99%
“…Moreover, the studies of Segel et al have demonstrated that the untranslated regions of PEG10 can be reprogrammed by inserting functional mRNAs of certain genes. By developing this system of selective endogenous encapsidation for cellular delivery (SEND), specific RNAs can be addressed, e.g., for therapeutic purposes [132].…”
Section: Viral Fusogensmentioning
confidence: 99%
“…Nevertheless, Peg10 also maintains the ability to bind and package its own mRNA. This finding allowed to create an artificial packaging system where heterologous RNAs fused with Peg10-3 UTR were efficiently packed by Peg10 [200,201]. Furthermore, using the viral RNA packaging system, it became possible to specifically incorporate sgRNA with the CRISPR-Cas9 nuclease into EVs for genome editing [202].…”
Section: Exploitation Of Viral Sorting Mechanisms For Rna Loading Into Evsmentioning
confidence: 99%
“…Nevertheless, Peg10 also maintains the ability to bind and package its own mRNA. This finding allowed to create an artificial packaging system where heterologous RNAs fused with Peg10-3'UTR were efficiently packed by Peg10 [199,200]. Furthermore, using the viral RNA packaging system it became possible to specifically incorporate sgRNA with the CRISPR-Cas9 nuclease into extracellular vesicles for genome editing [201].…”
Section: Exploitation Of Viral Sorting Mechanisms For Rna Loading Into Extracellular Vesiclesmentioning
confidence: 99%